Greenland, Boyd's ship, Veslekari at Bontekoe Island, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1933)
Fig. 87 - The Veslekari anchored to pack ice off Bontekoe Island. July 16, 1933. (III). (Caption from Boyd, L. A. (1935). The Fiord Region of East Greenland (pp. 79). New York: American Geographical Society) Veslekari in pack ice. See Fiord Region of East Greenland, p. 79. Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society